2018
DOI: 10.1037/spq0000246
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of a universal screening multiple gating procedure: A replication study.

Abstract: The purpose of this diagnostic accuracy study was to evaluate the sensitivity and specificity (among other indicators) of three universal screening approaches, including the Social, Academic, and Emotional Behavior Risk Screener (SAEBRS), a SAEBRS-based teacher nomination tool, and a multiple gating procedure (MGP). Each screening approach was compared to the BASC-2 Behavioral and Emotional Screening System (BESS), which served as a criterion indicator of student social-emotional and behavioral risk. All data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Practitioners could also consider providing professional development for secondary teachers to better recognize mental health concerns in their students or inclusion of student self‐report at the middle school level (e.g., see Green et al, 2017; Kilgus et al, 2018). Other implications from this study could include training for teachers, matched to student and school needs, to ensure consistency across ratings on the SRSS‐IE.…”
Section: Discussionmentioning
confidence: 99%
“…Practitioners could also consider providing professional development for secondary teachers to better recognize mental health concerns in their students or inclusion of student self‐report at the middle school level (e.g., see Green et al, 2017; Kilgus et al, 2018). Other implications from this study could include training for teachers, matched to student and school needs, to ensure consistency across ratings on the SRSS‐IE.…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence suggests that overall, universal screening may be the most effective method of identification; however, the rate of false-positive results yielded by this method is high (Auger, 2000; 2004; Husky et al ., 2011), so the expectations of teachers, pupils, and parents would need to be managed accordingly. Some findings indicate that multistage models are more accurate (Scott et al ., 2009; Morey et al ., 2015; Sweeney et al ., 2015); however two studies reported that a single assessment with a universal screening measure is sufficient to accurately identify high-risk individuals, and additional assessments and informants do not improve accuracy (Dowdy et al ., 2016; Kilgus et al ., 2018). Teacher nomination yields a higher number of false negative results than universal screening (Campbell, 2004; Dwyer et al ., 2006; Eklund et al ., 2009; Dowdy et al ., 2013; Cunningham and Suldo, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Twelve studies compared identification rates from universal screening and school staff nomination models (Tisher, 1995; Auger, 2000; 2004; Campbell, 2004; Dwyer et al ., 2006; Eklund et al ., 2009; Scott et al ., 2009; Dowdy et al ., 2013; Cunningham and Suldo, 2014; Kieling et al ., 2014; Sweeney et al ., 2015; Kilgus et al ., 2018). In four studies positive identification outcomes were verified by subsequent clinical interview (Auger, 2000; 2004; Scott et al ., 2009; Kieling et al ., 2014; Sweeney et al ., 2015), while remaining studies reported rates of overlap in identification between screening and staff nomination.…”
Section: Rates Of Accurate Identificationmentioning
confidence: 99%
See 2 more Smart Citations